Differences in the influence of daily behavior on health among older adults in urban and rural areas: evidence from China - Liu, Weizhong; Zheng, Renjie; Zhang, Yu; Zhang, Wang (Frontiers in Public Health, 2023)
As the population of older adult in China keeps growing, the degree of aging is becoming increasingly serious and the health of older adults is a growing concern. Comparing the personal characteristics and health levels of urban and rural older adults and determining the relationship between these factors are of great significance in maintaining their health. In addition, exploring how these relationships differ between urban and rural areas is important.This study conducted a literature review to examine the impact of various factors on the physical and mental health of older adults in urban and rural areas in China. Moreover, based on cross-sectional data from the 2017 Chinese General Social Survey (CGSS), urban-rural differences in the factors' degree of influence on the perceived health of older adults were studied using multiple logistic regression.Results: Regular physical exercise had a powerful protective effect on urban older adults' physical and mental health, whereas regular participation in social activities had a positive impact on rural older adults' health. Low income, low educational level, low social trust, lack of a partner, and having more than one child negatively affected the physical health of rural older people. Low socioeconomic status had a negative impact on rural people's health both in mind and body. Overall, the rural adults' health status was found to be relatively low and deserves more attention.This study demonstrated that older people's physical and mental health levels can be significantly affected by the frequency of daily activities and individual and family characteristics. Furthermore, urban-rural differences were observed. These findings could provide feasible suggestions for governments, communities, and older adults' family members to help alleviate health inequality.